The Areas of Teacher Research in the Sultanate of Oman and the Reality of Benefiting from Them - Suleiman S. Al-Husseini; Sulaiman S. Al-Ghattami; Rashid M. Al-Hajri (Sultan Qaboos University, 2018)
The present study aims at understanding the reality of teacher research in the Sultanate of Oman, how to benefit from such research in the improvement of teacher development and the teaching-learning process, who should do that, as well as informing current literature with updates on teacher research, a topic that is not yet given adequate attention in Oman. The study implemented a qualitative approach for data collection and analysis of 50 researches done by school-teachers and 22 interviews with research teachers, school head-teachers and educational specialists. The study revealed that teachers are interested in doing research. Teachers, school administration and supervisors benefit from teacher research. Teachers use their own ways to take advantage from their own research and to share it with other teachers and help them value its results and recommendations. The study recommends that a culture of teacher research should be founded in schools, teachers should be supported to do research and more research should be done to explore the extent to which teacher research meets the  criteria of educational research so that it can be trustworthy and useable for schooling improvement.